STRATEGI KOMUNIKASI PEMASARAN INDIHOME MEDAN DALAM MENARIK MINAT PELANGGAN - Nursapia Harahap, Syahrul Abidin, Ayuningtyas Wibowo Putri, (At-Tazakki: Jurnal Kajian Ilmu Pendidikan Islam dan Humaniora, 2023)
Abstract: This study aims to find out how Indihome Medan's marketing communication strategy attracts customer interest. This study used descriptive qualitative method. The theory used in this study is the IMC (Integrated Marketing Communication) theory. Data collection techniques used are observation, interviews, and documentation. Data analysis techniques used in this research are data collection, data reduction, data presentation and conclusion. The results of this study indicate that Indihome Medan's marketing communication strategy is in attracting customer interest through attractive offers and providing good benefits so that customers are interested in using Indihome products. The offer was made by distributing brochures, as well as outreach to people in the city of Medan regarding the benefits and advantages that Indihome has in helping telecommunication networks.